Semi-Asynchronous Hierarchical Federated Learning over Mobile Edge Networks - Chen, Qimei; You, Zehua; Wu, Jing; Liu, Yunpeng; Jiang, Hao (IEEE access, 2023)
Mobile edge network has been recognized as a promising technology for future wireless communications. However, mobile edge networks usually gathering large amounts of data, which makes it difficult to explore data science efficiently. Currently, federated learning has been proposed as an appealing approach to allow users to cooperatively reap the benefits from trained participants. In this paper, we propose a novel Semi-Asynchronous Hierarchical Federated Learning (SAHFL) framework for mobile edge networks that enables elastic edge to cloud model aggregation from data sensing. We further formulate a joint edge node association and resource allocation problem under the proposed SAHFL framework to prevent personalities of heterogeneous devices and achieve communication-efficiency. To deal with our proposed Mixed integer nonlinear programming (MINLP) problem, we introduce a distributed Alternating Direction Method of Multipliers (ADMM)- Block Coordinate Update (BCU) algorithm. With this algorithm, a tradeoff between training accuracy and transmission latency has been derived. Numerical results demonstrate the advantages of the proposed algorithm in terms of training overhead and model performance.